Symbolic Analysis of Animal Images in Edgar Allan Poe’s Works - Wang, Chao; Xiao, Xiaoyi; Xiao, Xiaoyi; Liu, Bao; Liu, Bao (Advances in Social Sciences Research Journal, 2018)
Edgar Allan Poe (1809-1849) is an influential writer in the history of American literature and even in world literature. He is a novelist, a poet and a literary theorist, who is known as a pioneer of horror fiction, science fiction and detective fiction. The style of his works is unique and fills with rich connation and it involves dual personality and non-communication between people. In particular, the animal images account for most proportion in his all works, and this is the focus of this thesis. The present study is to analyze some typical animal images in Poe’s works from the perspective of symbolism. Animal images in Poe’s literary works are divided into two categories for analysis. One is about the real-world animals, which suggest the darkness and complexity of human nature and reveal people’s living state and psychological state. Poe uses these animal images as tools to show a certain person’s personality or instinct and manifest the inner world or spirit situation of social beings. The other group concerns the virtual unknown animal images, such as gold bug. In his works, Poe expresses the desire of mankind to know themselves and the world. This study is supposed to analyze the symbolic meaning and functions of animal images, weather the real ones or the imaginable one in Poe’s works, which is expected to expand the perspective of animal image analysis in Edgar Allan Poe’s works, and provide a broader development space for the study of Edgar Allan Poe. It helps to deepen readers’ understanding of human nature and human life in Edgar Allan Poe’s works.